Using Immunization Coverage Rates for Monitoring Health Sector Performance : Measurement and Interpretation Issues - Bos, Eduard; Batson, Amie (World Bank, Washington, DC, 2013)
Immunization against childhood diseases such as diphtheria, pertussis, tetanus, polio and measles is one of the most important means of preventing childhood morbidity and mortality. Despite the low cost of basic childhood immunizations, nearly 3 million children still die each year from vaccine-preventable diseases. Achieving and maintaining high levels of immunization coverage must therefore be a priority for all health systems. In order to monitor progress in achieving this objective, immunization coverage data can serve as an indicator of a health system's capacity to deliver essential services to the most vulnerable members of a population. This note discusses the use of trends in immunization coverage data, and argues that immunization is a health output with a strong impact on child morbidity, child mortality and permanent disability. This note discusses measurement and interpretation issues for coverage data collected through surveys and administrative records.